AB0545 Effect of empathy nursing on the life quality of thepatients with systemic lupus erythematosus. (15th June 2017) - Wen, Y; Yan, L; LiMin, L
Abstract : Background: The patients with Systemic Lupus Erythematosus always had sub-health status in psychology and been troubled by the chronicity of the disease. Empathy nursing is an effective treatment for chronic disease such as cancer or terminal patients. Objectives: To investigate the effect of empathy nursing on the life quality of patients with Systemic Lupus Erythematosus (SLE). Methods: 120hospitalized patients with SLE admitted from January 2014 to December 2016 were divided into the control group and the experimental group for 60 people in each randomly. The control group was given routine care and the experimental group was given additional empathy care for 6 months. The World Health Organization Quality of Life (WHOQOL-BREF) Chinese version was evaluated on the 2nd day of hospitalization and 6 months after discharge respectively. Results: Before intervention, the life quality of the two groups was poor. The scores of the control group and the experimental group in each field had no statistic difference (44.13±16.72 vs 44.08±17.33 in physiology, 51.13±14.38 vs 52.01±13.87 in psychology, 58.12±15.33vs 56.71±8.12in social relation, 54.93±13.2 vs 55.33±11.78 in environment and 52.52±15.6vs 52.03±13.44 overall), (P>0.05). After the intervention, the scores of the WHOQOL-BREF scale in the two groups were improved to different extents (P<0.05) (59.33±13.76 vs 66.77±16.21 in physiology, 57.43±7.88 vs 64.55±11.76 in psychology, 65.22±13.34 vs 72.11±8.12 in social relation and the overall scores were 59.95±14.32 vs 67.89±6.42).The scores of the four dimensions in physiology, psychology, social relations and environment were significantly different from those before the intervention (P<0.05). The improvement of the scores in physiology, psychology, social relations in the experimental group was more obvious than the control group (P<0.05). Conclusions: Empathy nursing can obviously improve the life quality of SLE patients, and it is worthy to be popularized. References: Empathy - can it be taught? Jeffrey D, Downie R.J R Coll Physicians Edinb. 2016 Jun;46(2):107–112. Communication Needs of Patients with Breast Cancer: A Qualitative Study. Khoshnazar TA, Rassouli M, Akbari ME, Lotfi-Kashani F, Momenzadeh S, Rejeh N, Mohseny M. Indian J Palliat Care. 2016 Oct-Dec;22(4):402–409. Disclosure of Interest: None declared